2020
DOI: 10.1038/s41390-020-0813-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary fat intake and the risk of congenital heart defects in offspring

Abstract: Background Fatty acids are crucial in embryologic development, including cardiogenesis. The impact of maternal periconceptional dietary fat intake on the risk of congenital heart defects (CHDs) has not been clearly elucidated. We hypothesized that maternal dietary fat intake during pregnancy is associated with risk of CHDs in offspring. Methods We analyzed CHD cases and non-malformed controls from the National Birth Defects Prevention Study, a case-control, multicenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies from other Asian countries and the western world also report higher fat intake among pregnant and lactating mothers [ 31 , 32 ]. It is imperative to understand that high fat intake is associated with the risk of preeclampsia in women and congenital heart defects in the offspring [ 33 , 34 ]. The dietary intake of women during the postnatal phase is equally important, as the intake during pregnancy, which supports the demand associated with lactation and ensures optimal early life nutrition for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other Asian countries and the western world also report higher fat intake among pregnant and lactating mothers [ 31 , 32 ]. It is imperative to understand that high fat intake is associated with the risk of preeclampsia in women and congenital heart defects in the offspring [ 33 , 34 ]. The dietary intake of women during the postnatal phase is equally important, as the intake during pregnancy, which supports the demand associated with lactation and ensures optimal early life nutrition for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…Another study tested maternal triglyceride (TG) levels during early pregnancy, but only limited cases of CHD were included 4 . In contrast, a large case–control study based on the multicenter population‐based National Birth Defects Prevention Study reported that maternal periconceptional dietary fat intake did not increase the odds of CHD after adjusting for total energy intake 5 . However, the food‐frequency questionnaire, which is used to assess nutrient intake during the year before pregnancy, was completed at an average of 11 months after delivery 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 In contrast, a large case–control study based on the multicenter population‐based National Birth Defects Prevention Study reported that maternal periconceptional dietary fat intake did not increase the odds of CHD after adjusting for total energy intake. 5 However, the food‐frequency questionnaire, which is used to assess nutrient intake during the year before pregnancy, was completed at an average of 11 months after delivery. 5 It remains controversial whether maternal lipid profile is associated with CHD risk in offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Recently, emerging studies have substantiated the key effect of maternal metabolic disorder during pregnancy on the incidence of fetal CHD and have revealed that a high-fat diet contributes to CHD through multiple pathways. 1 , 8 , 9 In the current study, Zhao et al. 1 demonstrated via clinical analysis and in vitro and in vivo investigations in mouse models that increased maternal serum palmitic acid (PA) levels led to CHD by post-translational modification of GATA4, unveiling a new potential molecular target for prenatal prophylaxis of CHD.…”
Section: Main Textmentioning
confidence: 84%